(untitled) (Global Journal of Human-Social Science, 2016)
The modern state of the Sochi region of Russian Black seacoast is parsed in the article from the point of view of beaches stability, efficiency executed of the coastal protective measures, and quality of seawater in the coastal zone. The possible influencing on an environment of engineering measures, foreseen General schema of the coastal and landslide measures on coastal zone of Greater Sochi of 1990 is considered. The offers on organization of complex monitoring of the coastal zone are made.